Metacognition and Its Relationship With Orbitofrontal Cortex and Thalamus Volumes in Patients With Obsessive-Compulsive Disorder - Atmaca, Murad; Yildiz, Sevler; Taskent, Ismail; Tabara, Muhammed Fatih; Gurok, Mehmet Gurkan; Korkmaz, Sevda; Yildirim, Hanefi (Wiley, 2025)
PurposeThe study aims to explore the relationship between orbitofrontal cortex (OFC) and thalamus volumes and metacognition in patients with obsessive-compulsive disorder (OCD). By analyzing structural MRI data and metacognitive measures, it investigates how brain volume variations correlate with dysfunctional beliefs and OCD symptoms.MethodThe study consisted of 20 patients with OCD and 20 healthy controls. Yale-Brown Obsession Compulsion Scale (Y-BOCS), Metacognition Questionnaire-30 (MCQ-30), Hamilton Depression Scale (HAM-D), and Hamilton Anxiety Scale (HAM-A) were administered to OCD patients and healthy controls. They then underwent structural MRI scans to measure the volume of the OFC and thalamus.FindingOn both sides, OCD patients had smaller volumes of OFC than healthy control individuals, and their thalamic volumes were similar to those of the control participants. Furthermore, MCQ-30 scores showed a substantial negative correlation with left OFC volume.ConclusionIn conclusion, we suggest that dysfunctional metacognitive beliefs might be related to the occurrence of OCD, and these beliefs might be associated with the left side of OFC neuroanatomically.
Keywords: metacognition | obsessive-compulsive disorder (OCD) | orbitofrontal cortex (OFC) | thalamus